Firm age and the demand for marginal employment in Germany - Jochen Späth (Institut für Angewandte Wirtschaftsforschung (IAW), 2013)
Many empirical studies point towards an increase in non-standard employment. The reasons for this rise are mainly seen in the increasing economic internationalization or the rapid technological changes which raise the need for both flexibility and cost-cuts on behalf of firms. Yet, only little is known about the role of firm age in this context. Based on a large representative data set of establishments in Germany, this paper analyzes how establishment age impacts on the demand for marginal employment, the main form of non-standard employment in Germany. We find an inverted U-shape relationship between firms' share of marginal employment and their age indicating that the demand for marginal employment peaks during the middle ages of a firm, which can be explained by both the liabilities of newness and aging. Distinguishing between the extensive and intensive margin by using hurdle models, we find again an inverted U-shape relationship between the probability of having marginally employed workers and establishment age, which coincides with our previous results. However, a further kind of establishment seems to exist in that among those which have at least one marginal employee, young firms have most of them. Taking into account effects of the sample composition, we find that, although the very old establishments in our sample exhibit an equally low share of marginal employment as young establishments, the effect of young firms on the grand share of marginal employment is larger because of their larger number.
Keywords: J82; L26; L41; O33; 330; start-ups; firm age; job quality; flexibility; non-standard employment; marginal employment; hurdle model